Levels of subject communication in fiction literature - A. S. Komarov (Vestnik MGIMO-Universiteta)
The article is devoted to personality intercourse between writer and reader in Belles-Lettres. The intercourse between the self of the writer and the self of the reader realizes itself in the processes of writing and reading belles-lettres texts that serve as specific mediators between the two selfs. The article shows the free and personal nature of the intercourse. In the article, the author singles out and gives descriptions of stages/levels of involvement into belles-lettres personality intercourse. The author distinguishes five conventional stages: superficial or shallow stage, contradiction or conflict stage, identity or emotional stage, transcendental stage and supersensitive stage. Degree of openness of selfs to each other and degree of willingness on the part of the participants to express their own selfs serve as criteria of separating one stage from another. Degree of openness of selfs to each other is represented as a degree of the reader's openness to the writer's influence. While degree of willingness to express one's own self is perceived as a degree of the writer's or reader's readiness to reveal their self. The author argues that at each stage of intercourse its participants demonstrate a different degree of their involvement into it, which leads to misinterpretations of texts on the part of the reader and on the whole to misunderstanding between the reader and writer. The reader's transition from one stage to another can have a gradual character. However, the reader's transition to the writer's stage of intercourse can also be instantaneous, which depends on the reader's individual ability of perception as well as the writer's skill. The author of the article comes to the conclusion that understanding or misunderstanding between writer and reader as well as different interpretations of the writer's belles-lettres work by the reader lie at different stages in a degree of the reader's involvement into the intercourse suggested to him/her by the writer. In cases when both parties find themselves at one and the same stage of personal involvement the intercourse between them results in agreement of the written text and its interpretation by the reader. Thus, the writer acquires their readership while the reader discovers the writer who responds to his/her individuality.